2020
DOI: 10.3390/ijms21197005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of a Dendrobium officinale Geraniol Synthase DoGES1 Involved in Floral Scent Formation

Abstract: Floral scent is a key ornamental trait that determines the quality and commercial value of orchids. Geraniol, an important volatile monoterpene in orchids that attracts pollinators, is also involved in responses to stresses but the geraniol synthase (GES) responsible for its synthesis in the medicinal orchid Dendrobium officinale has not yet been identified. In this study, three potential geraniol synthases were mined from the D. officinale genome. DoGES1, which was localized in chloroplasts, was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The results indicated that the expression patterns of CfTPS may be regulated by MeJA treatment and may respond to multiple environmental stresses ( Chaiprasongsuk et al, 2018 ). In recent studies, MeJA was shown to regulate TPS gene expression in D. officinale and C. sinensis ( Yu et al, 2020 ; Zhao et al, 2020 ; Zhou et al, 2020 ). However, this needs to be further investigated in C. faberi .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the expression patterns of CfTPS may be regulated by MeJA treatment and may respond to multiple environmental stresses ( Chaiprasongsuk et al, 2018 ). In recent studies, MeJA was shown to regulate TPS gene expression in D. officinale and C. sinensis ( Yu et al, 2020 ; Zhao et al, 2020 ; Zhou et al, 2020 ). However, this needs to be further investigated in C. faberi .…”
Section: Discussionmentioning
confidence: 99%
“…In recent reports, DoTPS10 in D. officinale can convert GPP to linalool in vitro ( Yu et al, 2020 ). DoGES1 in D. officinale can catalyze geraniol in vitro and in vivo ( Zhao et al, 2020 ). Linalool and geraniol belong to monoterpenes which play essential roles in floral scents.…”
Section: Discussionmentioning
confidence: 99%
“…In D. officinale , with 34 TPS genes, 13 TPS genes were obtained in WGCNA analysis. The function of DoTPS10 has been verified; located in chloroplasts, DoTPS10 uniquely converted geranyl diphosphate to linalool in vitro ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among terpenes, geraniol is commercially important and is involved in plant–pollinator interaction and stress biology in nature. Zhao et al identified DoGES1 , a gene which encodes geraniol synthase, using genomic annotation data of D. officinale [ 8 ]. The authors studied the subcellular localization and functions of DoGES1 and finally concluded that DoGES1 was highly expressed in the petals of semi-open flowers and effectively controlled geraniol biosynthesis in D. officinale .…”
Section: Functional Genomics In Secondary Metabolites and Polysacchar...mentioning
confidence: 99%